Sistema de recirculação e rotina de manejo para larvicultura de camarões de água doce Macrobrachium rosenbergii em pequena escala - Valenti, Wagner Cotroni [UNESP]; Mallasen, Margarete; de Barros, Helenice Pereira (Inst Pesca, 2009)
A recirculating system and a matching management schedule for small-scale freshwater prawn larviculture were described. The system comprised a 140 L larval culture tank in line with a 43 L biofilter filled with 24 L of calcareous substrate. Both the tank and biofilter were made of black colored fiberglass in a conical-cylindrical shape. The turnover rate of the water through the system was 24 times a day; water was pumped by airlift. Results of ten larvicultures showed that the system maintained temperature, dissolved oxygen, pH, salinity, ammonium and nitrite stable and suitable to Macrobrachium rosenbergii larvae. Survival and productivity varied from 60.5 to 72.4% and 37 to 72 post-larvae/L, respectively; both were compatible with results of commercial hatcheries. Therefore, this system may be very useful for research purposes or adapted for small-scale post-larvae production.
Recirculating system and management schedule for small-scale freshwater prawn Macrobrachium rosenbergii hatchery
Keywords: Macrobrachium; freshwater prawn; hatchery; recirculating system; biofilter; management